Parental tuning of language input to autistic and nonspectrum children - He, Angela Xiaoxue; Luyster, Rhiannon J.; Arunachalam, Sudha (Frontiers in Psychology, 2022)
Caregivers’ language input supports children’s language development, and it is often tuned to the child’s current level of skill. Evidence suggests that parental input is tuned to accommodate children’s expressive language levels, but accommodation to receptive language abilities is less understood. In particular, little is known about parental sensitivity to children’s abilities to process language in real time. Compared to nonspectrum children, children on the spectrum are slower to process language. In this study, we ask: Do parents of autistic children and those of nonspectrum children tune their language input to accommodate children’s different language processing abilities? Children with and without a diagnosis of autism (ages 2–6 years, N = 35) and their parents viewed a display of six images, one of which was the target. The parent labeled the target to direct the child’s attention to it. We first examined children’s language processing abilities by assessing their latencies to shift gaze to the labeled referent; from this, we found slower latencies in the autistic group than in the nonspectrum group, in line with previous findings. We then examined features of parents’ language and found that parents in both groups produced similar language, suggesting that parents may not adjust their language input according to children’s speed of language processing. This finding suggests that (1) capturing parental sensitivity to children’s receptive language, and specifically language processing, may enrich our models of individual differences in language input, and (2) future work should investigate if supporting caregivers in tuning their language use according to children’s language processing can improve children’s language outcomes.